FAKTOR PENYEBAB KEJADIAN ANEMIA PADA IBU HAMIL DI UPTD PUSKESMAS KEMALARAJA KABUPATEN OGAN KOMERING ULU TAHUN 2018 - Yeviza Puspitasari (STIKES Abdurrahman. Pusat Informasi dan Manajemen, 2019)
Anemia is a major cause of maternal mortality and fetus during childbirth, due to bleeding. Maternal mortality in Indonesia is the highest in ASEAN, which is about 307 from 100 thousand births. Other ASEAN countries such as Malaysia, only 40-50% of the approximately 100 thousand births.